Radio-interferometric Monitoring of FRB 131104: A Coincident AGN Flare, but No Evidence for a Cosmic Fireball - Shannon, Ryan; Ravi, V. (Institute of Physics Publishing, 2017)
The localization of fast radio bursts (FRBs) has been hindered by the poor angular resolution of the detection observations and inconclusive identification of transient or variable counterparts. Recently a ?-ray pulse of 380 s duration has been associated with FRB 131104. We report on radio-continuum imaging observations of the original localization region of the FRB, beginning three days after the event and comprising 25 epochs over 2.5 years. We argue that the probability of an association between the FRB and the ?-ray transient has been overestimated. We provide upper limits on radio afterglow emission that would be predicted if the ?-ray transient was associated with an energetic ?-ray burst. We further report the discovery of an unusual variable radio source spatially and temporally coincident with FRB 131104, but not spatially coincident with the ?-ray event. The radio variable flares by a factor of 3 above its long-term average within 10 day of the FRB at 7.5 GHz, with a factor-of-2 increase at 5.5 GHz. Since the flare, the variable has persisted with only modest modulation and never approached the flux density observed in the days after the FRB. We identify an optical counterpart to the variable. Optical and infrared photometry, and deep optical spectroscopy, suggest that the object is a narrow-line radio active galactic nucleus. © 2017. The American Astronomical Society. All rights reserved.